THE USAGE OF THE WORD “PLAGUE” IN ENGLISH LITERARY TEXTS - Matluba Baxronova Axmedovna (Web of Journals Publishing, 2024)
Disease-related terms are frequently employed in oral and creative works in all languages, in addition to scientific terminology. They are priceless because they represent the distinct viewpoint, way of life, religious and cultural beliefs, background, and customs of every nation. Finding out the unique characteristics of their written creative speech, stylistic-functional speech, and lexical-semantic speech is crucial. The article covers the definition of the word "plague" in both literal and metaphorical senses, its derivation, artistic depiction of the word in these contexts, its metaphorical use in English literary examples, and the expressions and idioms derived from it.
Keywords: disease, plague, meaning, plague, epidemic, symbolism, social pain, medieval English literature, pestis, disease.